Vegetarian Diet Was Associated With a Lower Risk of Chronic Kidney Disease in Diabetic Patients - Hou, Yi-Chou; Huang, Hui-Fen; Tsai, Wen-Hsin; Huang, Sin-Yi; Liu, Hao-Wen; Liu, Jia-Sin; Kuo, Ko-Lin (Frontiers in Nutrition, 2022)
Introduction Diabetes mellitus (DM) is a pathological hyperglycemic state related to the dysregulation of insulin. Chronic kidney disease (CKD) is a common chronic complication in diabetic patients. A vegetarian diet could be one of the preventive strategies for the occurrence of CKD in patients with diabetes mellitus. However, it is still unknown whether a vegetarian diet lowers the occurrence of CKD in DM patients. Research Design and Methods This retrospective study was conducted at Taipei Tzu Chi Hospital from 5 September 2005 to 31 December 2016. Subjects with an HbA1c level > 6.5% or previous history of diabetes mellitus elder than 40 years were grouped based on self-reported dietary habits (vegetarians, lacto-ovo vegetarians and omnivores) in the structured questionnaire. Structural equation modeling (SEM) was applied to estimate the direct and indirect effects of variables on the occurrence of chronic kidney disease. Results Among these 2,797 subjects, the participants were grouped into dietary habits as vegans (n = 207), lacto-ovo vegetarians (n = 941) and omnivores (n = 1,649). The incidence of overall CKD was higher in the omnivore group [36.6% vs 30.4% (vegans) and 28.5% (lacto-ovo vegetarian), p < 0.001]. In the SEM model, after adjusting for age and sex, the lacto-ovo vegetarian [OR: 0.68, 95% confidence interval (CI): 0.57–0.82] and vegan groups (OR 0.68, 95% CI: 0.49–0.94) were both associated with a lower risk of CKD occurrence than the omnivore group. The vegan diet and lacto-ovo diet lowered the risk related to a high BMI (OR: 0.45, p < 0.001, OR: 0.58, p < 0.001) and hyperuricemia (OR: 0.53, p < 0.001; OR: 0.55, p < 0.001) for the occurrence of CKD. Conclusion Vegetarian dietary habits were associated with a lower occurrence of CKD in DM patients.